Multiscale Modeling of Mechanical Response of Carbon Nanotube Yarn with Orthotropic Properties Across Hierarchies - Aref Mehditabar; Hossein Esfandian; Seyed Sadegh Motallebi Hasankola (Computation)
This study aims to comprehensively evaluate the mechanical performance of dry-spun twisted carbon nanotube (CNT) yarns (CNTYs) subjected to uniaxial tensile load. To this end, in contrast to earlier approaches, the current research lies in an innovative approach to incorporating the orthotropic properties of all hierarchical structures of a CNTY structure. The proposed bottom-up model ranges from nanoscale bundles to mesoscale fibrillar and, finally, microscale CNTYs. The proposed methodology distinguishes itself by addressing the interplay of constituents across multiple scale levels to compute the transverse properties (orthotropic nature). By doing so, rigidity and mass equivalent principles are adopted to introduce a replacement of the model by converting the truss structure containing two-node beam elements representing (vdW) van der Waals forces in a nanoscale bundle and inclined narrower bundles in mesoscale fibrillar used in previous works to the equivalent shell model. Followed by the evaluation of mechanical properties of nanoscale bundles, they are translated to the mesoscale level to quantify its orthotropic properties and then are fed into the microscale CNTY model. The results indicate that the resultant CNT bundle and fibrillar exhibit much lower transverse elastic modulus compared to those in the axial direction reported in the prior literature. For the sake of validation of the proposed method, the reproduced overall stress–strain curve of CNTYs is compared to that attained experimentally, showing excellent correlation. The presented theoretical approach provides a valuable tool for enhancing the understanding and predictive capabilities related to the mechanical performances of CNTY structures.